The Effects of Financial Technology, Financial Attitude, and Financial Literacy on Financial Management Behaviors - Putri, Intan Uriana; Aisjah , Siti (Jurnal Management Risiko dan Keuangan, 2025)
In the modern era characterized by economic complexity and rapid technological advances, an individual's ability to manage finances becomes very crucial. The objective of this quantitative research is to analyze the impacts of financial technology, financial attitudes, and financial literacy on the financial management behaviors. The objects are undergraduate students of Universitas Brawijaya. This research uses a quantitative approach with multiple linear regression analysis methods. The data of this harvested from 5-point Likert-scaled closed questionnaires. The sample used in this research was 100 respondents with the criteria of being undergraduate students of Universitas Brawijaya batches of 2021 and 2022, still in the age range of 17-25 years, and having used financial technology products at least 2 products. The results of the multiple linear regression analysis indicate that the three independent variables positively influence the students’ financial management behavior. This research shows that increasing financial literacy, forming positive financial attitudes, and wise use of financial technology can encourage healthier financial management behavior among students.